Impacts of the Covid-19 pandemic on the audit of local government financial statements: experience from Indonesia - Ritonga, Irwan Taufiq (Taylor & Francis, 2022)
This article investigates the effects of the Covid-19 pandemic on the audit of local government financial statements in Indonesia. Auditors were only able to perform limited, simple audit procedures due to the large-scale social restrictions. Auditors completed their statutory audits by compromising in terms of accepting a higher audit risk, being more tolerant towards material misstatements and giving clean opinions.